The force stability of tissue contact and lesion size index during radiofrequency ablation: An ex‐vivo study. Issue 3 (5th March 2020) - Parwani, Abdul S.; Hohendanner, Felix; Bode, David; Kuhlmann, Stefan; Blaschke, Florian; Lacour, Philipp; Heinzel, Frank R.; Pieske, Burkert; Boldt, Leif‐Hendrik
Abstract: Introduction: Radiofrequency (RF) ablation is a commonly used tool in the invasive electrophysiology laboratory to treat a variety of rhythm disorders. Reliable creation of transmural ablation lesions is crucial for long‐term success. Lesion size index (LSI) is a multiparametric index that incorporates time, power, contact force (CF), and impedance data recorded during RF ablation in a weighted formula and has been shown to predict the extent of myocardial tissue lesions. Whether the force stability of contact influences lesion size in LSI‐guided ablations is unknown. Objectives: The aim of this study was to analyze the influence of the force stability of contact on lesion size during LSI‐guided ablations in an ex‐vivo model. Methods and Results: A total of 267 RF lesions (n = 6 hearts) were created on porcine myocardial slabs by using an open‐tip irrigated ablation catheter with the following settings: 35 W with either intermittent (varied between 0 and up to 20 g), variable (10 to 20 g), or constant tissue contact (15 g) in a perpendicular or parallel fashion (applied manually) up to a target LSI of either 5 or 6. Subsequently, lesion width and depth were determined. Lesion width was mainly influenced by catheter tip orientation and LSI, whereas lesion depth was mainly influenced by LSI alone. The force stability of catheter contact had no relevant impact on lesion width or depth. Conclusion: The force stability of catheter contact has only little effect on lesion depth or width in LSI‐guided catheter ablation while the catheter orientation primarily affects lesion width.